Wan Junaidi realistic on security - Ujang, Azman (The Sun, 2014)
I DON'T see why people should take issue with remarks by Deputy Home Minister Datuk Wan Junaidi Tuanku Jaafar over the insecurity of the remote diving islands off Sabah which have over the years been easy targets for kidnappers from the Philippines just across the watery border.